Strength and Ductility of Bubbled Wide Reinforced Concrete Beams with Diverse Types of Shear Steel Plates - Mohamed Ibrahim, Amer; Abdullah Mansor, Ahmed; D. Salman, Wissam; Jaafar Hamood, Mohammed (International Journal of Engineering and Technology, 2018)
This paper presents an experimental investigation on the strength of bubbled wide reinforced concrete beams with different types of shear steel plates. Eight specimens with dimensions of 215x560x1800mm were investigated. The studied variables deal with replacement of 10mm stirrups diameter stirrups spaced at 125mm by shear steel plates having equivalent cross-sectional area for stirrups at mid legs height with circular opening of different thicknesses (3, 4 and 5mm). Four specimens were without any bubbles and the others with bubbles. This study showed that the shear steel plates is a good alternative for replacing the stirrups and gives increasing in yield, ultimate load and deflection (at service load) with 5% , 15% and 9% on the average when using the bubbles. Without using bubbles, the aspect ratio of shear steel plates bounded between the boundaries 4.5 to 8 gave increased the ductility by 36%. Using the bubbles in specimens was decreased 4.7% from the total weight of specimens. ACI 318-14(1) and EC 2(2) codes give a predicted deflection more than that obtained from experimental results by 16% on the average and by 24% when using bubbles.Â Â  Â